Adaptasi Sosial Ekonomi Masyarakat terhadap Perubahan Kondisi Ekonomi di Kabupaten Puncak, Provinsi Papua Tengah - Tandinus Murib; Miswanto Miswanto; Frasto Biyanto; Baldric Siregar (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Economic transformation has encouraged indigenous communities in peripheral regions to strengthen their socio-economic adaptation in order to sustain their livelihoods. This study aims to examine the effects of external pressure and local social institutions on the socio-economic adaptation of communities in Puncak Regency, Central Papua, with community internal capacity acting as a mediating variable. A quantitative explanatory research design was employed using data collected from 200 respondents selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that external pressure, local social institutions, and community internal capacity have positive and significant effects on socio-economic adaptation. Community internal capacity also partially mediates the relationships between external pressure, local social institutions, and socio-economic adaptation. These findings highlight the importance of strengthening community capacity and local institutions to support adaptive and sustainable development policies in peripheral regions.